The Importance of Farmer Regeneration in the Future Modernization of Agriculture in Southeast Aceh District - Prastika Prastika (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Southeast Aceh Regency has a huge potential to bring its agricultural sector to a better level in all aspects. However, several obstacles still hinder the sustainability of agriculture in our country. Therefore, it is imperative to reform agricultural products by using technology for yield and efficiency in agriculture. Young people are the most competent in modernizing technology nowadays. Agricultural regeneration related to agricultural product reform is important to involve the elderly and the younger generation in improving productivity. However, there are problems with farmer regeneration caused by various reasons in the southeast Aceh district. The purpose of this study is to determine how farmer regeneration can impact agricultural products and modernize agriculture going forward. A descriptive qualitative research method was used along with a literature review strategy. In addition, secondary data sources such as books, journals and other references, previous research were also used to support the research. The data analysis techniques used include data reduction, data presentation, and conclusion drawing. The results of this study are strategies aimed at parents and the younger generation of farmers must be carried out to encourage better regeneration of farmers. Regeneration of farmers to modernize agriculture can be done by providing agricultural education and training.